Modeling and control of a two-axis fast steering mirror with piezoelectric stack actuators for laser beam tracking. (4th June 2015) - Zhu, Wei; Bian, Leixiang; An, Yi; Chen, Gangli; Rui, Xiaoting
Abstract: This paper outlines an optical beam steering system built using a two-axis fast steering mirror (FSM) with piezoelectric stack actuators to maintain precise pointing control. A novel mathematical model of the FSM is put forward by using a transfer matrix method of a multibody system to describe the dynamics characteristics and a hysteresis model to represent the hysteresis. Based on the proposed model, a model-based hybrid control is applied to force the output angle of the FSM to track the laser beam accurately thereafter. The experimental results are in accordance with the theoretical analysis. The results highlight significantly improved accuracy in the beam tracking control of the FSM.